Enhancing New Student Enrollment Using an Integrated SWOT-QSPM Approach: A Case Study of XYZ University - Hisbulloh Ahlis Munawi; Indung Sudarso (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
Competition in the service industry, especially higher education, is becoming increasingly intense. This tight competition also affects University XYZ, resulting in a declining number of new students. The purpose of this study is to identify weaknesses, strengths, opportunities, and threats through a SWOT analysis, and to evaluate strategies using QSPM. The SWOT analysis results indicate that the main strategy involves utilizing reputation, diverse study programs, experienced lecturers, and high-achieving students to seize opportunities such as the increasing interest in pursuing higher education. The QSPM analysis shows that the SO strategy has a TAS value of 6.43, the ST strategy has a TAS value of 5.99, the WO strategy has a TAS value of 5.45, and the WT strategy has a TAS value of 5.21. The integration of both analyses results in implementable strategies for increasing new student enrollment, ensuring that the strategies can be effectively applied.